Pseudomonas aeruginosa endophthalmitis caused by accidental iatrogenic ocular injury with a hypodermic needle. (April 2017) - Lu, Cheng-wei; Hao, Ji-long; Liu, Xiu-fen; Liang, Ling-ling; Zhou, Dan-dan
Iatrogenic traumatic endophthalmitis is a rare but serious ocular infection that can lead to severe vision loss. A 44-year-old man presented with pain and decreased vision in the right eye 4 hours after injury with a hypodermic needle during irrigation of his eye. Slit-lamp examination revealed a penetrating corneal puncture and iris hole in the right eye. Twenty hours later, his visual acuity had decreased to hand motion, and severe fibrinoid uveitis was noted. He immediately underwent irrigation of the anterior chamber and intravitreal antibiotic injection. The right eye became painful again, and emergent vitrectomy combined with lensectomy was performed along with intravitreal antibiotic administration. The patient remained stable during the 2-month follow-up. Standard practice should be adopted when irrigating the eye to prevent this type of injury, and emergent surgical intervention is very important to preserve visual function.